A bargaining model of migration: getting the permission of the farm household. In: Rob B. Dellink and A. Ruijs (eds.) - Mensah-Bonsu, A.; Burger, K. (Economics of Poverty, Environment and Natural Resource Use. - The Netherlands : Springer, Dordrecht, pp. 185-208., 2008)
The chapter models migration decisions as joint individual and family decisions and develops a model in which family members can migrate on the condition that they remit more than they would have contributed as resident household member. The upper bound on remittances is set by their own net benefits after migration. The paper uses cross-sectional data collected in 2000 from northeast Ghana to investigate the effect of farm household population, family landholding and the perceived soil quality on migration and remittance decisions of members of the farm household in Northeast Ghana. Nested logit and Tobit models estimation techniques are employed. The empirical results confirm the negative effect that per-capita farmland size has on the probability of migration. More livestock sales coincide with fewer remittances. The core factors of the theoretical model could not be confirmed, however Land quality appears to have no effect on migration or remittances. Local employment conditions help mitigate migration, however.
Keywords: Migration; Remittances; Soil quality; Man/land ratio; Bargaining